Decoupling Gender Injustice in China's Divorce Courts - Michelson, Ethan (Social Sciences, 2022)
Anyone interested in courts, judicial decision-making, family law, gender violence, and the limits and possibilities of the globalization of law will want to read this book about women's struggles to divorce in China's court system. This title is also available as Open Access on Cambridge Core.